'Strangers to themselves': Ageing, the Individual, and the Community in the Fiction of Iris Murdoch, John Banville, and John McGahern. Issue 2 (November 2018) - Ingman, Heather
Abstract : Irish literary gerontology has been slow to develop and this article aims to stimulate discussion by engaging with gerontologists' assertions that ageing in a community of peers is enriching. Juxtaposing the experience of ageing individuals in the novels of Iris Murdoch and John Banville with the more social experiences of John McGahern's protagonists, the article finds parallels between Murdoch's The Sea, The Sea (1978) and Banville's fiction with its emphasis on the ageing individual, invariably male, who attempts to fashion a coherent identity through narration. By contrast, McGahern's The Barracks (1963), is focused through the eyes of a female protagonist whose final months are shaped by interaction with the society around her, while in That They May Face the Rising Sun (2002) ageing is experienced through an entire community.